Perubahan Patologis Hepar Akibat Cemaran Aflatoksin B1 Pada Pakan Ayam Pedaging Komersial Di Kota Kupang - Devi Y. J. A. Moenek; Aris Haryanto; Charles Rangga Tabu (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Aflatoxin B1 is a secondary metabolite of Aspergillus flavus, Aspergillus parasiticus, and Penicillium puberulum fungus, which is frequently found as contaminants of feed/raw materials of poultry feed. Such compounds have toxic and carcinogenic effects that can cause damage to various tissues/organs, which can further decrease the performance of broiler and cause various degrees of immunosuppressive effects. This study was designed to evaluate the most common pathological lesion in the liver of commercial broiler after consumption of aflatoxin contamination feed in Kupang City of East Nusa Tenggara Province. The research was conducted on 10 broiler farms in Kupang City. Samples of liver were taken for further processing according to the staining method of haematoxylin and eosin (H&E). The results of pathological examination of tissues were analyzed descriptively. Based on the results of this experiment, it can be concluded that pathological examination on the liver showed an early-stage of liver cirrhosis, atrophy of bursa fabricius, thymus and lien due to the necrosis and depletion of lymphocytes.